Halomonas smyrnensis as a cell factory for co-production of PHB and levan - KASAVİ, CEYDA; TOKSOY ÖNER, EBRU; HACIOSMANOĞLU, GÜL GÜLENAY; EROĞLU, MEHMET SAYIP; GENÇ, SEVAL; CAN, ZEHRA SEMRA (ELSEVIER SCIENCE BV, 2018)
Levan is a fructan type polysaccharide that has long been considered as an industrially important biopolymer however its limited availability is mainly due to the bottlenecks associated with its large-scale production. To overcome such bottlenecks in the commercialization of this very promising polysaccharide, co-production of levan with polyhydroxyalkanoates (PHAs) by halophilic Halomonas smyrnensis cultures has been proposed in this study for the first time. After in silico and in vitro assessment of PHA accumulation, fermentation profiles for levan and PHA concentrations were obtained in the presence of sucrose and glucose and the PHA granules observed by TEM were found to be poly(3-hydroxybutyrate) (PHB) after detailed structural characterization by GC-MS, DSC, FTIR and NMR. Six nutrient limitation strategies based on nitrogen (N) and phosphorus (P) were tested but highest levan and PHB yields were obtained under unlimited conditions. H. smyrnensis is proved to co-produce PHB and levan while using inexpensive carbon sources which is a commercially successful microbial cell factory system showing a great potential in lowering manufacturing costs and aiming for a zero waste policy within the biorefinery concept. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Halomonas smyrnensis; Polyhydroxyalkanoates; PHB; Levan; Co-production; Halophiles; HYDROXYBUTYRATE-CO-HYDROXYVALERATE; BIOMEDICAL APPLICATIONS; HALOPHILIC BACTERIUM; MELTING BEHAVIOR; MULTILAYER FILMS; POLY(3-HYDROXYBUTYRATE); STRAIN; WASTE; BIOPOLYESTERS; STRATEGIES